Pendekatan Tri Hita Karana Dalam Meningkatkan Motivasi Berwirausaha Mahasiswa - Ni Kadek Yuliandari; Ni Nyoman Sunariani (Universitas Pendidikan Nasional, 2020)
ABSTRACTThis research is used to find out more about the philosophy of Tri Hita Karana in improved students entrepreneurship motivation in STIE Satya Dharma Singaraja, by used lecturer and students as informants. This research is qualitative descriptive with approach case study. The results showed that the understanding of the philosophy of THK able to encourage the entrepreneurial spirit by promoting fairness as a reflection of aspects parahyangan, implement and uphold the work ethic of Hindus as a reflection of aspects pawongan, and always uphold the attitude of protecting and maintaining the environment as a reflection of aspects palemahan. With the foundation of the philosophy of THK, believed to be able to create an atmosphere that is harmonious and balanced in business.